2010
DOI: 10.1227/01.neu.0000369193.03305.00
|View full text |Cite
|
Sign up to set email alerts
|

Choroid Plexus Metastasis From Papillary Thyroid Carcinoma Presenting With Intraventricular Hemorrhage

Abstract: Choroid plexus metastasis from papillary thyroid carcinoma is very rare, and this is the first case of intraventricular hemorrhage reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…CPM lesions originating from thyroid carcinoma are extremely rare, with only five cases reported thus far (8)(9)(10)(11)(12). In this report, we described the sixth such case; all six cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…CPM lesions originating from thyroid carcinoma are extremely rare, with only five cases reported thus far (8)(9)(10)(11)(12). In this report, we described the sixth such case; all six cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 79%
“…Wasita et al reported that, in their case, the tumor was initially not recognized because it was obscured by the focal IVH. One month later, following blood reabsorption, the tumor was identified and removed (11). In our case, CT revealed the IVH, and we planned endoscopic hematoma evacuation, which ultimately could not be performed.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Different treatment modalities, such as radioiodine therapy, external beam radiation and surgery have been suggested and used in the limited number of cases [8]. In the present case, surgery was chosen because of the nature of the tumor.…”
Section: A B Pamukkale Tıp Dergisi 2013;6(2):104-106mentioning
confidence: 99%